2011
DOI: 10.1111/j.1365-2265.2011.04141.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between fat depot‐specific preadipocyte differentiation and metabolic syndrome in obese women

Abstract: This study identified that SC-preadipocyte differentiation is associated with metabolic syndrome independent of obesity, whereas OM-preadipocyte differentiation is not. These findings suggest that, in the setting of obesity, an enhanced adipogenic capacity of SC depots could be protective for metabolic syndrome. Our data underscores an interaction between adipose tissue homoeostasis and metabolic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 36 publications
(63 reference statements)
6
33
0
Order By: Relevance
“…Growing observations support the concept that IR is a pathophysiological cue initiated in, and sustained by, dysregulated fat (adipocentric view) [8,[18][19][20][21][22][23][24][25][26][27][28][29][30]. The main biological signatures that characterize the "unhealthy" fat organ are the following: (1) enlargement of existing fat cells; (2) selective impairment of insulin signaling in adipocytes (i.e., downregulation of IRS-1 and upregulation of mitogen-activated protein kinase (MAPK)-dependent signal); (3) adipose inflammation, characterized by extensive macrophage and lymphocyte infiltration; (4) limited angiogenesis; and (5) hampered adipogenic differentiation of the precursor cell.…”
Section: Impaired Adipogenesis and Metabolic Dysfunctions: Role Of Famentioning
confidence: 93%
See 1 more Smart Citation
“…Growing observations support the concept that IR is a pathophysiological cue initiated in, and sustained by, dysregulated fat (adipocentric view) [8,[18][19][20][21][22][23][24][25][26][27][28][29][30]. The main biological signatures that characterize the "unhealthy" fat organ are the following: (1) enlargement of existing fat cells; (2) selective impairment of insulin signaling in adipocytes (i.e., downregulation of IRS-1 and upregulation of mitogen-activated protein kinase (MAPK)-dependent signal); (3) adipose inflammation, characterized by extensive macrophage and lymphocyte infiltration; (4) limited angiogenesis; and (5) hampered adipogenic differentiation of the precursor cell.…”
Section: Impaired Adipogenesis and Metabolic Dysfunctions: Role Of Famentioning
confidence: 93%
“…The main biological signatures that characterize the "unhealthy" fat organ are the following: (1) enlargement of existing fat cells; (2) selective impairment of insulin signaling in adipocytes (i.e., downregulation of IRS-1 and upregulation of mitogen-activated protein kinase (MAPK)-dependent signal); (3) adipose inflammation, characterized by extensive macrophage and lymphocyte infiltration; (4) limited angiogenesis; and (5) hampered adipogenic differentiation of the precursor cell. Although the dynamics of these steps remains still intricate and not fully defined, the failure of (pre)adipocyte differentiation may well be the initial trigger in the development of unhealthy fat mass expansion [8,[18][19][20][21][22][23][24][25][26][27][28][29][30], which ultimately favors a diabetogenic milieu through various and partly synergistic mechanisms.…”
Section: Impaired Adipogenesis and Metabolic Dysfunctions: Role Of Famentioning
confidence: 99%
“…It is important to note that adipocyte dysfunction and ectopic fat deposition have been shown to precede the manifestation of T2D, which implies that this early defect is a causal event for T2D. Park et al compared the adipogenic potential of ex vivo cultured preadipocytes derived from subcutaneous fat depots of obese women with and without the MetS (Park et al, 2012). They found that healthy obese women had a significantly higher capability of preadipocyte differentiation than obese women suffering from the MetS.…”
Section: Adipocyte Dysfunction In Metabolic Disorders: Manifestationmentioning
confidence: 99%
“…Its function in both physiological and immunological processes may be influenced by either tissue-resident adipocytes or the stromal vascular fraction, which includes leukocytes, mesenchymal stem cells, adipocyte progenitors, fibroblasts, and macrophages [22]. Here we characterized SVC composition and homeostatic gene expression profile of leukocytes based on lymphocyte (R1) versus monocyte/granulocyte (R2) fractions revealed a 6:1 ratio [23].…”
Section: Discussionmentioning
confidence: 99%